Consolidation of the Journal Investigación y Educación en Enfermería as a Publication with Impact on the Dissemination of Nursing Knowledge - Rodríguez Gázquez, María de los Ángeles (Investigación y Educación en Enfermería, 2024)
Almost 14 years ago, Dean Beatriz Elena Ospina Rave entrusted me with the direction of the IEE Journal, given the leave of absence taken by the then director, María del Pilar Pastor, who had been named Secretary of Health of the Municipality of Medellín. Meeting this responsibility represented a great academic and professional challenge because it was a scientific publication of the highest quality in the area of Nursing, recognized in Colombia and Latin America. I received a journal with 26 years of uninterrupted edition and which already had three years in category A2 in the PUBLINDEX by COLCIENCIAS, hence, I had the commitment to lead the preparation of the publication to ascend to the long-awaited maximum A1 category, for which it was “only” necessary to meet the most complex criterion to obtain: achieve indexing in Medline, or in at least one of the bibliographic citational bases, like Elsevier’s Scopus or in the Web of Science, now Clarivate.